Gambaran Penggunaan Obat Antihipertensi pada Pasien Preeklampsia di Instalasi Rawat Inap Rumah Sakit Bhayangkara Kota Palangka Raya Tahun 2016 - Syahrida Dian Ardhany (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Preeclampsia and eclampsia are the second rank cause of maternal mortality, and the first is bleeding. Therefore, the initial diagnosis of preeclampsia, which is the beginning of eclampsia, and its treatment needs to be immediately implemented to reduce maternal and child mortality. This study aims to know the description of antihypertensive preeclampsia in Bhayangkara Hospitals of Palangka Raya to review of an aspect of the accurate indication, the right drug, right patient, and the right dose of the reference JNC 7. This type of research is nonexperimental research. The study was done by observation which the data was taken retrospectively and analyzed by descriptive non-analytic. The result showed that the type of drug used was 80% of methyldopa, 60 % nifedipine, MgSO4 60% and of evaluation of drug use in Bhayangkara Hospitals of Palangka Raya in 2016 did not find any indication, drug, dose, and patient that not right.